Applications of informatics in veterinary medicine - Smith, Ronald D. (Medical Library Association, 2000)
This study used the peer-reviewed biomedical literature to define the veterinary informatics knowledgebase and associated subspecialties, and assesses the level of activity in the field over the thirty-year period from 1966 through 1995. Grateful Med was used to search the MEDLINE bibliographic database for articles that shared one or more Medical Subject Headings (MeSH) keywords from the veterinary and medical informatics subject headings. Each of ninety-five MeSH medical informatics terms was assigned to one of twelve veterinary informatics subspecialties. The number of articles retrieved by each MeSH keyword and subspecialty was calculated. A total of 611 articles were retrieved, representing the contributions of 1,338 authors published in 153 journals. The field experienced slow growth over the twenty-year period from 1966 through 1985. In the following decade, the cumulative number of veterinary informatics articles almost tripled and the percentage of veterinary-related articles that included an informatics component increased almost two-and-one-half fold. Despite this recent growth, the number of veterinary-related articles with an informatics component has never exceeded 1% of either the veterinary or medical informatics literature over the past thirty years, and representation of veterinary subspecialties in the literature varied widely.